Perception and attitudes of medical students toward communication, chronic disease and death - Ghodke, Baliram V.; Ray-Mohanty, Ipseeta; Wagh, Abhay R.; Deshmukh, Yashwant A. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Medical students of today’s world found difficulty in communication when they faced with dying patients, how they would feel, what are their perception about caring of patients with chronic disease. These are often unspoken and neglected issues. Methods: It was a cross-sectional comparative questionnaire based survey of the 2nd year medical students and interns. Students were evaluated using a questionnaire consisting of 15 Likert type statements. Results: Completed questionnaire received from 89 out of 100 students. All students strongly agreed upon the commutation with patients. Interns (37.03%) were strongly disagreed (p=0.001) on not curing the patient is a failure of doctors. Interns (32.58%) were significantly more likely to be less worried (p<0.01) about death of the patient and to indicate cancer is a non-curable disease (p<0.001) when compared to 2nd MBBS. Students from both the groups distressed, while communicating with dying patients and relatives of dying patients. Conclusion: Perception of students regarding caring of chronically ill-patients and death related issues needs improvement. We believe that integrating different teaching strategies and training programs regarding this issue should begin at early stages of undergraduate medical curriculum.